Comparative Evaluation of Green Tea Pretreatment on Serum Biochemical Markers in Gentamicin-Induced Nephrotoxicity among Long Evans Rats (Journal of Rangpur Medical College, 2026)
Background: Aminoglycoside antibiotic gentamicin is a widely used clinical agent with nephrotoxicity that is dose related. The pathogenesis of kidney injury that occurs due to drugs is based on oxidative stress. Objective: Methods: The experimental in vivo study was carried out from 1st July 2019 to 30th June 2020 in Sir Salimullah Medical College, Dhakawhere 30 healthy male Long Evans rats aged between 90-120 days. Statistical analysis was done using SPSS v22 with ANOVA and post hoc Bonferonni test (p _ 0.05). Results: Green tea pretreatment significantly reduced the gentamicin-induced increases in serum creatinine (1.02±0.12 vs 1.54±0.16 mg/dL, p